Nephrotoxicity Due to Snake Bites - Srikandi, Ni Made Putri Rahayu; Ayu, Nyoman Paramita (Green Publisher Indonesia, 2025)
Snakebites remain a critical public health issue in tropical countries, particularly due to their severe systemic effects, including nephrotoxicity and acute kidney injury (AKI). One major complication that frequently arises from envenomation, especially from Viperidae and Elapidae species, is AKI, which can progress to life-threatening conditions if not promptly managed. This study aims to explore the clinical management of snakebite-induced AKI and its systemic complications, using a case study of a 51-year-old male patient. The research employs a qualitative clinical case approach, involving observational analysis, serial laboratory tests, imaging, and documented treatment progression. The patient, who presented with swelling and bleeding in the bitten limb, was diagnosed with stage 3 AKI, Disseminated Intravascular Coagulation (DIC), and thrombocytopenia. Management included administration of antivenom, hemodialysis, and blood product transfusions. Significant improvements in kidney function and coagulation parameters were observed within two weeks. The findings highlight the urgency of early intervention, particularly in cases where the snake species is unidentified. This study contributes to a deeper understanding of AKI pathophysiology in envenomation and underscores the importance of WHO and KDIGO guideline implementation. It also emphasizes the need for enhanced clinical training and protocols in resource-limited settings to improve outcomes in snakebite victims.